2007
DOI: 10.1111/j.1471-0528.2007.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graduated compression stockings on blood velocity in the deep venous system of the lower limb in the postnatal period

Abstract: Venous thromboembolism (VTE) is the leading cause of maternal mortality in the UK and is also a major cause of long-term morbidity. Recent UK national guidelines recommend thromboprophylaxis, which includes the use of graduated compression stockings (GCS), for high-risk women to reduce the risk of VTE in both the antenatal and postpartum period. This study of 17 women examined the effects of GCS on the deep venous system in the immediate postpartum period and found a statistically significant reduction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
1
26
0
1
Order By: Relevance
“…In addition, the lower surface-to-volume ratio in large veins and the reduced effectiveness of surface-bound coagulation inhibitors 48 must also be considered. Our analysis (shear rates were calculated here from the vein diameter and flow rate values measured by Jamieson et al 47 ) of published data 47 shows that the shear rate in the common femoral vein is increased by Ϸ50% by gradient compression stockings, a result that is consistent with this hypothesis. Although shear rate can be estimated by dividing the velocity of blood flow by the diameter of a blood vessel, assuming a circular, noncompressible tube, 33 the actual shear rate in blood vessels in vivo may be more difficult to calculate because of Figure 5.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the lower surface-to-volume ratio in large veins and the reduced effectiveness of surface-bound coagulation inhibitors 48 must also be considered. Our analysis (shear rates were calculated here from the vein diameter and flow rate values measured by Jamieson et al 47 ) of published data 47 shows that the shear rate in the common femoral vein is increased by Ϸ50% by gradient compression stockings, a result that is consistent with this hypothesis. Although shear rate can be estimated by dividing the velocity of blood flow by the diameter of a blood vessel, assuming a circular, noncompressible tube, 33 the actual shear rate in blood vessels in vivo may be more difficult to calculate because of Figure 5.…”
Section: Discussionsupporting
confidence: 79%
“…4,46 Although various anticoagulants contribute to the prevention of venous thromboembolism, 2 increased blood flow rate and velocity are usually interpreted as possible mechanisms by which compression stockings prevent DVT. 16,47 However, we hypothesize that shear rate may be a better predictor of initiation of coagulation than volumetric flow rate or flow velocity, because a considerable amount of coagulation is initiated on or near vessel walls, and the flow velocity approaches zero on the vessel walls. In this respect, large veins may be more risky because, for a given flow rate or flow velocity, their shear rates are disproportionately low.…”
Section: Discussionmentioning
confidence: 99%
“…GCS are commonly used as a thromboprophylaxis adjunct in pregnancy and postpartum, while IPCD can be used during and after caesarean section. A small Scottish study found a reduction in lumen size of the common femoral vein and increase in blood velocity after application of GCS in the immediate postnatal period after vaginal delivery (Jamieson et al, 2007). Despite the general lack of evidence for their use in pregnancy, the RCOG advises the use of GCS in postpartum women where there are three or more risk factors present (Nelson-Piercy et al, 2009).…”
Section: Mechanical Thromboprophylaxismentioning
confidence: 99%
“…50 In a Cochrane review of nine randomly controlled studies, 3% (n ¼ 598) who received GCS with prophylaxis developed DVT compared to 14% (n ¼ 595) in the control group. When compression stockings were used without anticoagulation, seven randomly controlled studies revealed 15% (n ¼ 536) developed DVT versus 29% (n ¼ 491) of the control group.…”
Section: Mechanical Prophylaxismentioning
confidence: 99%